The mechanisms of struvite biomineralization in municipal wastewater - Leng, Yirong; Soares, Ana (Elsevier, 2021)
The mechanisms of struvite production by biomineralization were investigated for five microorganisms (Bacillus pumilus, Brevibacterium antiquum, Myxococcus xanthus, Halobacterium salinarum and Idiomarina loihiensis) in municipal wastewater. The microbial exponential phase of growth occurred within the first 48 h of incubation, with growth rates varying from 0.02–0.08 1/h. These five microorganisms removed 23–27 mg/L (66–79%) of ortho-phosphate from wastewater, which was recovered as biological struvite (i.e., bio-struvite) identified by morphological, X-ray diffraction and elemental analysis. Bio-struvite crystals occurred in a low extracellular supersaturation index (0.6–0.8 units). Bio-struvite formation in B. pumilus M. xanthus, H. salinarum cultures was linked to biologically induced mineralization. Whereas B. antiquum and I. loihiensis produced bio-struvite through biologically controlled mineralization mechanism because the crystals presented homogeneity in morphology and size, and intracellular vesicle-like cell structures were observed enclosing electron-dense granules/materials. Nutrient recovery through biomineralization has potential application in wastewater streams promoting circularity within the wastewater industry.
Keywords: Municipal wastewater; Intracellular cluster; Phosphorus recovery; Struvite; Biomineralization